PERANAN HAKIM DALAM MENJATUHKAN PUTUSAN TERHADAP ANAK PELAKU TINDAK PIDANA PENGGUNA NARKOTIKA - NUR SARI DEWI (Universitas Sumatera Utara, 2013)
Children are potential young generation to continue the ideals of national struggle. With their strategic role and special characteristics, children can ensure the continuous existence of the state and nation in the future. Children who are in conflict with law need protection considering that they are immature and very much depending on others. Basically, children cannot protect themselves from various mental, physical and social threats in their lives, especially in the implementation of chils criminal justice they are infamiliar with.The application of criminal law as a means of preventing drug abuse will eventualy result in the problem how a judge make his decision. The basic consideration for the judge to make decision that can be used as the materials to analyze the orientation of the judge in making decision is also very important to see how releveant the decision the judge has made to the predetermined purpose of punishment. In sentencing the children using drug, the judge tends to base it more on juridical consideration. Juridical consideration is not adequate to be the only base in sentencing children. It will be wiser if the sentence is based on the non-juridical consideration such as the children’s spiritual, mental and physical growth because this spiritual ability is the base for the judges including the judge who sentences the children.